Early pre-season changes in the countermovement jump outcome and strategy variables of english super league rugby players - McMahon, J. J.; Comfort, P.; Jones, P. A.; Cuthbert, M.; Badby, A. J. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to quantify changes in typical (i.e., jump height) and alternative (i.e., jump momentum) countermovement jump (CMJ) outcome and strategy variables, alongside maximal strength, during the early English Super League pre-season period. Twenty professional senior male rugby league players from an English Super League club performed CMJ and isometric mid-thigh pull (IMTP) testing (3 trials of each) on portable dual force plates on the first and last day of pre-season training held prior to a short Christmas break (December 2021). Select CMJ outcome and strategy variables and both absolute and relative (to body mass) peak force for the IMTP trials were automatically calculated via proprietary software. IMTP peak force significantly increased in both absolute and relative terms (moderate effects; g = 0.69) reflecting the aims of the pre-season training programme. Countermovement depth moderately reduced (r = 0.76) but time to take-off and reactive strength index modified remained unchanged. A small but non-significant increase in body mass was noted, which, along with increased jump height (small effect; g = 0.46), contributed to a significant, moderate increase in jump momentum (g = 0.59). Quantifying concomitant changes in CMJ outcome and strategy variables, alongside body mass, during pre-season training may offer richer insight into rugby league players` future physical development requirements beyond jump height alone.